Factors Shaping First-Time Voter Choices Among Santri and Students in Tapal Kuda Area, East Java, Indonesia - Moh Syaeful Bahar; Mohammad Rifan Firmansyah (JURNAL AT-TURAS, 2026)
This study examines the voting behavior of first-time voters among santri and students in the Tapal Kuda, region within the broader context of democratic participation and local political dynamics in Indonesian East Java. The research addresses how socio-cultural, religious, and contextual factors shape electoral preferences among novice voters who are often influenced by communal ties and authority structures. The purpose of this study is to identify and analyze the key determinants that influence the voting behavior of first-time voters, particularly those affiliated with pesantren and secondary schools. This research employs a qualitative approach, using purposive sampling to select santri and student informants in the Tapal Kuda region. Data were collected through in-depth interviews, observation, and documentation, allowing for a holistic understanding of perceptions, awareness, and behavioral tendencies related to elections. The findings reveal that the voting behavior of first-time voters is shaped by multiple factors. First, political awareness and knowledge significantly influence the rationality of voting decisions. Second, candidate prominence, including social reputation, wealth, and religious knowledge, becomes an important consideration. Third, geographical proximity fosters familiarity and expectations of regional development benefits. Fourth, candidate performance, particularly physical appearance and perceived authority, affects voter preferences, especially among less politically mature voters. Fifth, emotional bonds derived from shared pesantren, school affiliations, organizational involvement, and kinship relations play a substantial role. Finally, religious considerations strongly shape voter choices, with candidates perceived as religiously knowledgeable gaining greater trust. These findings highlight the interplay between rational evaluation and socio-religious influences in shaping first-time voter behavior in the Tapal Kuda region.